Development and validation of the quality of online health information seeking: Psychometric properties and a confirmatory factor analysis - Engku Alwi, Sharifah Sumayyah; Azmi Murad, Masrah Azrifah; Abdullah, Salfarina; Kamaruddin, Azrina (Malaysian Journal of Library and Information Science, 2022)
This study aims to investigate the development and validation of all items and dimensions for the quality of online health information seeking (QHIS), which was assessed using a five-point interval self-report rating measure. This measure is proposed to evaluate the quality of online health information seeking among Malaysian consumers through confirmatory factor analysis (CFA). A total of 392 responses were collected from Malaysian consumers using the simple random sampling method. The pooled-CFA procedures were conducted to validate all dimensions at once. When the findings were acquired, the study performed the validation procedure for construct validity, convergent validity, composite reliability and discriminant validity. Results from CFA confirmed the validity of the QHIS measure by generating good data-model fit statistics characterised by strong latent construct and internal reliability estimates. Based on the self-reported scores, it also concluded that the QHIS scale had good convergent validity. The findings also reported that composite reliability and discriminant validity for all latent constructs in QHIS had been achieved accordingly. These findings present initial justification indicating that QHIS is reliable and valid and can be utilised to assess the quality of online health information seeking among Malaysian consumers. Limitations are explored, and recommendations for future research and practice are provided.